Factors affecting biochemical composition of seston in an eutrophic reservoir (Pampulha Reservoir, Belo Horizonte, MG - BOËCHAT,I. G. (2000)
Sestonic biochemical composition (lipids, proteins and carbohydrates) may change with varying environmental fluctuations. These changes and the effects in the nutritional status of algae consists of an actual increasing source of interest. The aims of this work were to establish the relationship between biochemical composition of seston and 1) a range of physical, chemical and climatological factors, and 2) the natural fluctuation in the species composition in phytoplankton assemblages of the Pampulha Reservoir, an urban eutrophic lake located in Belo Horizonte, MG. Seasonal changes in the biochemical composition were observed in this study. None of the considered abiotic factors alone seem to affect the biochemical composition. So the effects could only be understood by interactions among different environmental factors. On the other hand, the dominant algal groups probably have some influence in the observed changes in biochemical composition of seston.